Dynamic-Covalent Hydrogel with NIR-Triggered Drug Delivery for Localized Chemo-Photothermal Combination Therapy - Sun, Pengfei; Huang, Ting; Wang, Xiaoxiao; Wang, Gaina; Liu, Zhijia; Chen, Guosong; Fan, Quli (Biomacromolecules, 2020)
Near-infrared (NIR) light-responsive, injectable hydrogels are among the most promising drug delivery systems for localized anticancer therapy owing to its minimally invasive administration and remote-controlled manner. However, most currently reported NIR-responsive hydrogels were usually generated through physical mixing of thermosensitive polymers and photothermal conversion agents. In this study, a novel type of dynamic-covalent hydrogel (GelPV-DOX-DBNP) with NIR light-triggered drug release behavior was rationally designed for chemo-photothermal combination treatment of tumors. Concretely, this NIR-responsive hydrogel was formed by specific benzoxaborole-carbohydrate interactions between benzoxaborole (BOB)-modified hyaluronic acid (BOB-HA) and fructose-based glycopolymer (PolyFru), where photosensitizer perylene diimide zwitterionic polymer (PDS), reductant ascorbic acid (Vc), anticancer drug doxorubicin (DOX) as well as photothermal nanoparticles (DB-NPs) were encapsulated, simultaneously. Upon 660 nm light irradiation, both PDS and Vc within the designed hydrogel can convert oxygen into hydrogen peroxide, which could make hydrogel be degraded through the breakage of dynamic covalent bonds based on benzoxaborole-carbohydrate interactions, leading to NIR light-activatable release of DOX and DB-NPs from GelPV-DOX-DBNP. Furthermore, the released DB-NPs can convert 915 nm light irradiation into heat, enabling the application of GelPV-DOX-DBNP as a NIR-responsive drug delivery platform for both chemotherapy and photothermal therapy (PTT). In vivo results prove that GelPV-DOX-DBNP exhibited a markedly enhanced chemo-photothermal synergistic therapy for 4T1 tumor model mice, compared to chemotherapy alone or PTT. This work presents a new strategy to construct NIR light-responsive hydrogel as one alternative drug delivery system for anticancer applications.